Manajemen Program Kelas Kursus Peserta Didik di SMP Muhammadiyah 3 Bandar Lampung - Novianti, Novianti; Dermawan, Oki; Akmansyah, Akmansyah (Universitas Islam Negeri Raden Intan Lampung, 2022)
SMP Muhammadiyah 3 Bandar Lampung is one of the private schools that implements student grouping program management, with the course classes method for students. This study aimed to know about: 1)the planning of course program at SMP Muhammadyah 3 Bandar Lampung; 2)the implementation of course program at SMP Muhammadiyah 3 Bandar Lampung; and 3)the evaluation of course program at SMP Muhammadiyah 3 Bandar Lampung.The type of research was descriptive qualitative with data sources taken from the school principal, vice principal for curriculum, vice principal for student affair and vice principal for Islam, Muhammadiyah and Arabic language. Data collection techniques were taken from interviews, observation and documentation. Data analysis procedures consisted of data reduction, data presentation and data verification. The data validity was tested by triangulation, analysis and drawing conclusions.The results of this study were: first, the planning for student grouping program at SMP Muhammadiyah 3 Bandar Lampung wasdeveloped inthe meeting at the beginning of school year; and second, this implementation of the course was doneonce a week in the last hour after the school hour. The program consisted of Tahfidz class for memorizing verses of the Quran, with a target of adding 3 juz of memorization from the previous memorization. Meanwhile, the Arabic and English classes taught poetry, speech, conversation, debate, singing, games, news reading and storytelling. All of which were also prepared for competition, in addition to the main goal of the school to give students life skill in foreign languages. Third, the evaluation of the student grouping program was done during the school meetingat the end of the semester. A final test was given as the assessmentof the students and the results were included in the report card.